The switch from Gd-DTPA to Gd-DOTA is not associated with decrease of the T1 signal intensity of the pallidus and dentate in a pediatric population. (March 2021) - Gulino, Pietro; Bianchi, Andrea; Diciotti, Stefano; Scionti, Alessandra; Sali, Lapo; Papadopulos, Paulo; Mascalchi, Mario
Background: The switch from the linear gadolinium-based contrast agent (GBCA) gadopentate dimeglumine (Gd_DTPA) to the macrocyclic GBCA gadobutrol is associated with a decrease of the T1 signal intensity (SI) in brain gray matter nuclei. The effects of the switch to other macrocyclic GBCAs are not yet established. Purpose: To explore the effects of switching from Gd-DTPA to the macrocyclic GBCA gadoterate meglumine (Gd-DOTA) in pediatric patients. Material and Methods: We measured the pallidus/middle cerebellar peduncle (MCP) SI ratio and the dentate/MCP SI ratio in pre-contrast sagittal T1-weighted spin-echo images in nine patients who had received ≥6 administrations of Gd-DTPA and then of Gd-DOTA, in 18 patients who had received ≥6 administrations of Gd-DOTA alone, and in nine age-matched controls without prior GBCA administrations. Serial assessment was performed in patients who switched from Gd-DTPA to Gd-DOTA. Finally, the rate of change of pallidal/MCP and dentate/MCP SI ratios between the first and last Gd-DOTA administrations was compared. Results: The pallidal/MCP and dentate/MCP SI ratios were ( P < 0.05) higher in patients with prior Gd-DTPA and Gd-DOTA administrations compared to the controls. After the switch, the pallidal/MCP SI ratio increased in nine patients and the dentate/MCP ratio in seven patients. The rate of change of pallidal/MCP SI ratio after Gd-DOTA was higher ( P < 0.01) in patients who had previously received Gd-DTPA (mean 2.89 ± 2.6%) than in patients who had received Gd-DOTA alone (mean 0.53 ± 0.89%). Conclusion: T1 SI in gray matter nuclei does not decrease after switching from Gd-DTPA to Gd-DOTA. The switch effects from Gd-DTPA to each macrocyclic GBCA should be individually evaluated.